Analysis of Obstetric Medical Determinant Factors toward Mothers with the Stunting Children - Syahril, Erlin; Mappaware, Nasrudin Andi; Akib, Marliyanti; Mursyid, Muhammad (Green Medical Journal, 2020)
Introduction: Toddlerhood is a period that is very sensitive to the environment so more attention is needed especially the adequacy of nutrition. Nutrition problems, especially stunting in a toddler can inhibit the growth and development of the children. This study aimed to identify various obstetric medical characteristics and determine the obstetric medical determinant factors that most influence pregnant women with the incidence of stunting in Mamuju Regency, West Sulawesi. Methods: This study was conducted from June until August 2019 in Mamuju Regency, West Sulawesi. The total samples in this study were 88 people who were taken from mothers who had stunting toddlers aged 2-5 years old in Mamuju Regency, West Sulawesi. A total sampling method was used. A cross-sectional with the retrospective approach with a regression test. Data instruments were used questionnaires, observation sheets, and checklists. Results: The result of the stunting study was found from the toddler nutrient data from January until June 2020 in West Sulawesi by using total sampling. The researchers found a sufficient influence for the complication during childbirth factor, while the weak relation of the stunting based on the ages, parity, pregnancy spacing, poor obstetric history, comorbid disease, maternal surface, neonatal surface, hemoglobin levels, and the history of Sectio Caesarea (SC). Conclusion: One of the obstetric medical factors that have a sufficient relationship for causing the stunting for children is the complication during childbirth, while other obstetric medical factors have a very weak relation to the stunting case.